An Investigation Into Medical Waste Management Practices In Hospitals In Northern Peninsula Malaysia - OMRAN, Abdelnaser; MOHAMMED, Mohammed Khalifa Abdelsalam (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
The main aim of the study was toinvestigatethe medical waste management practices located in the north part hospitals in Malaysia. The northern part includes (Penang, Kedah, Perlis and Perak States). A questionnaire survey was mainly used for gathering information concerning different medical waste management aspects by identifying training services, segregation, and containers, storage, collection, transportation as well as ward attendants. Forty (40) hospitals (public and private) located in the above-mentioned stateswere targeted. The sample size of the whole study was 250 questionnaires; these questionnaires came from different hospitals where they located in the states of Penang, Kedah, Perlis, and Perak. As results, it was found from the analysis that although training programs were offered in the most places, there were not common centralized areas for training and even not applicable at all by 3.5% within the hospitals surveyed in Penang state accordingly to the administrative questionnaire. However, ongoing training programs either for old or new workers had been not identified. The responsibility for the waste to get segregated obviously not practiced by clear designated staff. Other numbers of problems that hospitals are facing in terms of medical waste managementinclude lack of sacks which are not totally subjected to tear, lack of provisional measures carried out to prohibit liquids running out from waste and not enough protective gear were used by workers. From the results of this study, it was clear that medical waste had not received sufficient attention according to WHO recommendation standard. Therefore, it was concluded that the majority of the examined areas had shown lack of practices in terms of segregation, collection, storage and transportation in dealing efficiently with medical waste management. In addition to that, all the interested parties (government, hospitals and workers at healthcare facilities) wrer recommended to implement a safe reliable medical waste management strategy, not only in legislation and policy formation but also particularly in its monitoring and enforcement, which can be achieved by the cooperation of Ministry of Health, Environmental Quality Authority, Ministry of Local Government, and Non-Governmental Organizations working in the same fields.